If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + y = 640 Solving 3x + y = 640 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1y' to each side of the equation. 3x + y + -1y = 640 + -1y Combine like terms: y + -1y = 0 3x + 0 = 640 + -1y 3x = 640 + -1y Divide each side by '3'. x = 213.3333333 + -0.3333333333y Simplifying x = 213.3333333 + -0.3333333333y
| (x-4)/(8-x)=0 | | (5x-1)(x-3)=0 | | (2x+5)+3x-10=70 | | 5x-45=15 | | 4r-3=r+2r+3 | | y=(x-1)(5x+2) | | 11=2x-7*1 | | 7*cos(x)=sin(x) | | 15.8x+10.4=12.0 | | .75(-16-8x)=.5(16-20x) | | 8.5x+5.4=17.3 | | 6+2v=-2 | | -3w+2w+7=-9 | | 4(9-9x)=-9(4x-4) | | -8.8(X-2.75)=26.4 | | -3=3+2v | | -500+10p=3500-10p | | 24x+6-4=4x+10 | | 0.35*x=1 | | 0.3*x=1 | | 1.2+0.3=0.9 | | (22X-1)(4X+5)(8X+3)(16X-15)-99X^2=0 | | 5x+4=24+17 | | y=-4-y | | sin^2(2x)=3sin(2x) | | 4/15-12a | | 6(y-4)+2(y+1)=4 | | 10x^2+20=325 | | 4x-8-2x=10 | | 3(x-4)-2(1-x)=0 | | 3p-2=p+18 | | 5z+9=8 |